2019
DOI: 10.1007/s11368-019-02349-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of soil water content and soil amendments on trace metal release and seedling growth in serpentine soil

Abstract: Purpose This study was conducted to evaluate the synergistic effects of organic amendments and soil water status on trace metal release from serpentine soil. Materials and methods Two organic amendments, dendro-biochar (BC) and municipal solid waste compost (CM), were added to serpentine soil at four different ratios, specifically 2.5:0.0, 2.5:1.0, 2.5:2.5, and 2.5:5.0% (w/w). Along with the control (with no organic amendments), each soil treatment was incubated separately under saturated point (SP) and field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…As related to soil moisture properties and metals, we found correlations between WP and Co (0.95), and WP and Mn (-0.86) in farm soils. In a similar study that investigated the effects of soil water status on metals in serpentine soil (Gunarathne et al, 2019), there was a positive relation between WP and Mn and Co. They attributed it to the microbial reduction that occurs by water deficiency below the WP.…”
Section: Correlations Between Soil Variables and Metalsmentioning
confidence: 95%
“…As related to soil moisture properties and metals, we found correlations between WP and Co (0.95), and WP and Mn (-0.86) in farm soils. In a similar study that investigated the effects of soil water status on metals in serpentine soil (Gunarathne et al, 2019), there was a positive relation between WP and Mn and Co. They attributed it to the microbial reduction that occurs by water deficiency below the WP.…”
Section: Correlations Between Soil Variables and Metalsmentioning
confidence: 95%
“…Studies reporting on the impact of in-field heavy metal stress on crop yield are still very limited, even though the studies reported here clearly show the impact of heavy metal pollution on crop yield, and the predominant data comes from greenhouse pot experiments or hydroponic experiments. Some experiments used irrigation water from mining sources to treat plants for biomass and yield analysis [ 43 ], and others used contaminated soils to grow plants for further analysis [ 44 , 45 ]. Hydroponic experiments, to test the impact of heavy metal stress on plant growth, have become an attractive method [ 46 , 47 ], but the method using soils (contaminated or uncontaminated) with heavy metal supplementation (spiking) remains the method of choice for crop biomass experiments.…”
Section: Heavy Metal Pollution Decreases Food Securitymentioning
confidence: 99%
“…Reports indicate that increased application of biochar in the root zone of soil deficient in phosphorus increases plant-available phosphorus concentration, increasing plant growth and phosphorus uptake by 59% and 73%, respectively (Meyer 2022). Biochar influences phosphorus mineralization and phosphatase enzyme activity, which is responsible for converting organic phosphorus into inorganic forms for uptake (Viraj et al 2019). Nutrients are labile and supplied through mineralization over time (Kammann et al 2015;Nele et al 2018;Schmidt et al 2015).…”
Section: Introductionmentioning
confidence: 99%